Building wet planets through high-pressure magma–hydrogen reactions - H. W. Horn; A. Vazan; S. Chariton; V. B. Prakapenka; S.-H. Shim (Nature, 2025)
Abstract Close-in transiting sub-Neptunes are abundant in our Galaxy 1 . Planetary interior models based on their observed radius–mass relationship suggest that sub-Neptunes contain a discernible amount of either hydrogen (dry planets) or water (wet planets) blanketing a core composed of rocks and metal 2 . Water-rich sub-Neptunes have been believed to form farther from the star and then migrate inwards to their present orbits 3 . Here we report experimental evidence of reactions between warm, dense hydrogen fluid and silicate melt that release silicon from the magma to form alloys and hydrides at high pressures. We found that oxygen liberated from the silicate melt reacts with hydrogen, producing an appreciable amount of water up to a few tens of weight per cent, which is much greater than previously predicted based on low-pressure ideal gas extrapolation 4,5 . Consequently, these reactions can generate a spectrum of water contents in hydrogen-rich planets, with the potential to reach water-rich compositions for some sub-Neptunes, implying an evolutionary relationship between hydrogen-rich and water-rich planets. Therefore, detection of a large amount of water in exoplanet atmospheres may not be the optimal evidence for planet migration in the protoplanetary disk, calling into question the assumed link between composition and planet formation location.